FishCoral-PRSA Information System for Albay Gulf - Balilo Jr., Benedicto B; Dioneda Sr., Ronnel R.; Vibar, Jayvee Christopher N.; Balmadrid, Davie B.; Sy, Darell James; Maraña, Hannah Louis L. (International Journal of Computing Sciences Research; Vol 4 No 2 (2020): Vol 4, No 2, 2020)
Purpose – The demand for the development of information systems provides a critical role in project management considering the call towards project automation. The study aims to develop and implement an information system (IS) used to managed the assessment results from socio-economic assessment, aquatic ecology and habitat, water quality assessment and capture fisheries of Albay Gulf.  The study utilized the features of Geographical Information System (GIS) to render the coordinates of sampling target sites for spatial referencing.  The Rational Unified Process (RUP) model was used to design the overall design, implementation and evaluation of the system. The source code of the developed program was used to develop the test cases the results showed that the internal and external characteristics of the developed system satisfied the standard functional system requirements.  Thus, the system offers the features of an information system and may serve as a model of future IS projects.  Information systems played a critical role in project management.  The purpose of the study is to develop an information system to database the participatory resource and socio-economic assessment (PRSA) of Albay gulf.  The system features managed the requirements for socio-economic, aquatic ecology and habitat, water quality and capture fisheries assessment.  The features of the Geographical Information System (GIS) used to render the coordinates for spatial referencing of targets of the different components.  The BFAR as the funding agency shall serve as the administrator of the system and in support Bicol University can help in the pilot testing of the developed system to partner agencies and various stakeholders. Method – The study used developmental type of research using Rational Unified Process (RUP).  The system used PHP applications, bootstrap framework and other tools to design the functional requirements of the system.  Black-box and White-box testing was used to analyze and validate the internal structures and functionalities of the system components including the full visibility of the logic and code structures. Results – This study generated the features for socio-economic, aquatic ecology and habitat, water quality and capture fisheries components.  Each component has its own user interface showing the assessment results, field activities and infographics.  Conclusion – The study provides effective and efficient interface for socio-economic assessment, aquatic ecology and habitat, water quality and capture fisheries assessment.  The application of geographical information system generated the geospatial location for coral reefs, seaweed/seagrass, and mangrove sample target areas.  Recommendations – The implementation of the system will help Government agencies like DA and BFAR secure the information (especially in projects like this) and serve as reference for future projects. Research Implications – The system is significant in providing updated information relating to socio-economic, aquatic ecology and habitat, water quality and capture fisheries which shall be used as policy support for Government and other stakeholders.